Autocrine and paracrine regulation of human T cell IL-10 production. - Cohen, S; Parry, S; Feldmann, M; Foxwell, B (1997)
We confirm that IL-10 is produced comparatively late after the activation of human T cells via CD3 stimulation, after IL-2 and IFN-gamma. Furthermore we show that IL-10 production by human T cell lines, such as IFN-gamma and IL-2, is inhibited by the immunosuppressive drugs cyclosporin A and FK506. However, a third immunosuppressive drug, rapamycin, normally associated with inhibiting the effects, but not the production, of cytokines, inhibited IL-10, but not IFN-gamma, production. This implies that IL-10 induction may be a secondary event in T cell activation. Since IL-2 is the major growth factor for T cells and is detected before IL-10, we focused on this factor as a potential activator of IL-10 production. We showed that IL-10 production by human T cell lines stimulated by immobilized anti-CD3 in the presence of neutralizing Abs to IL-2 and IL-2R (anti-CD25) was inhibited, whereas addition of exogenous IL-2 enhanced IL-10 production, indicating that IL-10 production by human T cells can be driven by stimulation via IL-2. As the IL-2R shares the common gamma-chain component with IL-4, IL-7, and IL-15, we investigated the possibility that they may all enhance anti-CD3-induced IL-10 production and established that this was the case. Since IL-10 has been previously described as a direct inhibitor of Ag presentation and of IL-2 production, our finding that IL-2 is capable of inducing its own inhibitor demonstrates a feedback mechanism within the immune system that could limit ongoing T cell activation and possibly inflammation.